On the Completion of Pro-$\mathcal{P}$ Groups - Ilić-Georgijević, Emil (Sarajevo Journal of Mathematics, 2024)
We examine the class of finite paragraded groups which we will denote by $\mathcal{P}.$ After observing that the class $\mathcal{P}$ is closed with respect to subgroups and direct products (\cite{7}), we define the notion of a pro-$\mathcal{P}$ group and consider the completion of such a group. 2000 Mathematics Subject Classification. 08A05, 16W50, 20L05, 20E18, 20-99